Community Empowerment Strategy in Bangkit Bersama Cooperation (Case Study of the Waste Management and Water Hyacinth Craftsmen Empowerment Program) - Ramadani, Rika Fitri; Akhyadi, Ade Sadikin; Heryanto, Nunu (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
This research is set out from the various empowerment strategies implemented in each community empowerment institution. Heterogeneous environmental conditions became a consideration in implementing empowerment strategies to the community. The empowerment strategy became the main capital to attract the attention of the community to take the empowerment program seriously. The purpose of this study is to describe the implementation of the empowerment strategies used at this institution. Cooperative is a forum for community empowerment in the economic field. This research was conducted because there was a uniqueness found in the empowerment program. This institution of empowerment did not only empower the community economically, but also socially, environmentally, and spiritually of the community. This study used qualitative methods of observation, interview, and documentation studies. The finding of this research was empowerment strategies using holistic development which in turn are able to develop community life dimensions in an integrated manner. The conclusion obtained from this study is that holistic development can create an independent, prosperous, and having the positive character